Using the flipped classroom to enhance EFL learning - Chen Hsieh, Jun Scott; Wu, Wen-Chi Vivian; Marek, Michael W. (Computer assisted language learning, 2017)
Instruction in English is a priority around the globe, but instructional methodologies have not always kept pace with the changing needs of students. To explore the benefits of the flipped classroom model for learners of English as a Foreign Language, the researchers used flipped learning and Wen's Output-driven/Input-enabled model to design a holistic oral training course that included extensive online written and verbal communication for the learning of a wide range of English idioms. The participants were 48 sophomore English majors in two required English oral training classes. A within-subjects research design exposed all participants to learning English idioms by flipped learning, using the LINE smartphone app, and by conventional instruction. A mixed research method was employed, using multiple sources of data collection, including pre- and post-tests on idioms, two questionnaires ("Perception of Flipped Learning Experience" and "Technology Acceptance Model"), the teachers' in-class observations, and semi-structured focus-group interviews. The results revealed that the theory-based flipped instruction using online written and oral interaction not only enhanced the participants' motivation, making them more active in using idioms in class, but also significantly improved their idiomatic knowledge, indicating that the flipped learning was successful in achieving the instructional goals of the class. The authors present insights into the impact of theory-based flipped learning on motivation and idiomatic acquisition; student impressions of the online platform used, LINE; and offer recommendations for practice.